STRENGTHENING DIGITAL LITERACY CULTURE BY UTILIZING THE JOURNAL OF ARABIC LANGUAGE EDUCATION STUDENTS OF AL-FALAH ASSUNNIYYAH UNIVERSITY KENCONG JEMBER - Furoidah, Asni; Zaeni, Ahmad; Tofaynudin, Johan Indrus (International Conference on Humanity Education and Society (ICHES), 2024)
Digital literacy is a person's ability to develop reading and writing potential by utilizing digital media access. The emergence of literacy activities is caused by the lack of digital reading and writing among students. Digital literacy includes elements of communication and collaboration in the form of active participation in learning, research and community service activities. The purpose of this research is to find a model of strengthening digital literacy carried out by Arabic Language Education students of Al-Falah Assunniyyah University Kencong Jember in the learning and research process. This research uses qualitative methods with the type of research is descriptive qualitative. While the research approach is in the form of field studies or field research. Data collection techniques in this research are by observation, documentation study and interviews with Arabic language education students. The results of this research show that (1) optimization of an-Nuqthah student journals provides many benefits for the development of digital literacy, (2) strengthening digital literacy culture can develop students' academic and non-academic intelligence. Thus, it can be concluded that the use of an-Nuqthah student journals can strengthen the literacy skills of Arabic Language Education students in the digital era.